The Use of Mind Mapping Technique to Improve the Students’ Writing Achievement and their Active Participation - Jannah, Nur Hidayatul; Tasnim, Zakiyah; Puspa, Areta (EFL Education Journal, 2024)
This research aimed to improve the students’ writing achievement and their active participation at one of the Islamic senior high schools in Mojoagung. The participants of this research were the tenth grade students of Social 1. There were 18 students as the research participants. The design of this research was classroom action research. The data collection methods were writing tests, observation checklists, and interviews. This research was carried out for 2 cycles, which consisted of two meetings for the treatment and one meeting for the writing test in each cycle to meet the standard research criteria. The students’ writing achievement improved from 33.3% in cycle 1 and 77.7% in cycle 2. On the other hand, there was an improvement in the students’ participation from 50% in cycle 1 to 86% in cycle 2. From the results of this research can be concluded that mind mapping technique could improve the students’ active participation and their writing achievement of descriptive text.